Inverse dynamic model and a control application of a novel 6-DOF hybrid kinematics manipulator - Pott, Peter Paul; Wagner, Achim; Badreddin, Essameddin; Weiser, Hans-Peter; Schwarz, Markus (Journal of automation, mobile robotics, & intelligent systems, 2011)
Kinematics with six degrees of freedom can be of several types. This paper describes the inverse dynamic model of a novel hybrid kinematics manipulator. The so-called Epizactor consists of two planar disk systems that together move a connecting element in 6 DOF. To do so each of the disk systems has a linkage point equipped with a homokinetic joint. Each disk system can be described as a serial 3-link planar manipulator with unlimited angles of rotation. To compensate singularities, a kinematic redundancy is introduced via a fourth link. The kinematic concept leads to several technical advantages for compact 6-DOF-manipulators when compared to established parallel kinematics: The ratio of workspace volume and installation space is beneficial, the number of kinematic elements is smaller, and rotating drives are used exclusively. For a singularity-robust control-approach, the inverse dynamic model is derived using the iterative Newton-Euler-method. Feasibility is shown by the application of the model to an example where excessive actuator velocities and torques are avoided.
Published online: 21 September 2010
Gesehen am 30.01.2020